Pyelolithotomy in a Patient with Complete Coraliform Calcification Induced by a Double-J Ureteral Stent. (28th May 2019) - Bonfitto, Miguel; de Oliveira Cury, Analaura; Caroline Pagelkopf, Victoria; Ramos Bezerra de Morais, Vinicius; Abib Cury, Carlos
Abstract : The placement of a double-J ureteral stent enables the treatment of upper urinary tract obstruction. Despite advances, forgetting the stent favors the occurrence of calcification, leading to increased morbidity rates, lawsuits, and a financial burden on the healthcare system. This paper describes a successful pyelolithotomy for the removal of a calcified double-J ureteral stent.